A Computing Methodology for Evaluating Supply Chain Competitiveness. (2018) - Verma, Ajay; Singhal, Nisha
Abstract: The objective of this paper is to discuss a factor based AHP methodology to enrich the evaluation of the supply chain competitiveness in the Indian manufacturing industries. The role and potential of AHP approach are discussed and it is suggested that comparison through the use of AHP can make the evaluation of supply chain competitiveness more effective and rational. At one level it tries to identify the factors of the supply chain competitiveness and at a more important level it evaluates these factors to be utilized for achieving supply chain competitiveness. This paper presents a factor based multi criteria decision making approach using AHP application as a tool to analyze a hierarchical model of supply chain competitiveness. The aim is to encourage more efforts in this regard for wider benefits and applications.